Хавчуу Ам Ордын Судалгаанд Геофизикийн Аргуудыг Хэрэглэсэн Байдал - Б, Билгүүн-Очир; Б, Бат (Scientific transaction of the National University of Mongolia. Physics, 2022)
When comparing the exploration results thus far from Khavchuu with those of known mineralisation and mineral deposits in the region. The occurrence of north to north-east trending, low angle, thrust faults which also coincide with resistivity and chargeability highs, magnetic lows, As anomalies and positive Au chip samples, issimilar to that observed and documented at Boroo. The resistivity anomalies generated have been interpreted as being associated with an area of silicification or quartz veining and from the dipole-dipole results these seem to occur as shallowly dipping structures similar to those hosting the Boroo mineralisation. The chargeability highs could be interpreted as regions of sulphide mineralisation and coincide with many of the anomalous areas again as with Boroo, although in the southern area the near surface chargeability low becomes a chargeability high with depth suggesting a degree of sulphide destruction during weathering in the upper regions. Magnetic lows could be interpreted again as zones of weathering and associated destruction of magnetite in granites or sulphides in mineralised regions. Assuming that any mineralisation at Khavchuu will exhibit a similar refractory component, this broad weathering could be of significant economic importance.